2021
DOI: 10.1111/pin.13098
|View full text |Cite
|
Sign up to set email alerts
|

KIFC1 regulates ZWINT to promote tumor progression and spheroid formation in colorectal cancer

Abstract: Funding informationTakeda Science Foundation; Japan Society for the Promotion of Science Colorectal cancer (CRC) is the second leading cause of cancer-related mortality worldwide. Kinesin Family Member C1 (KIFC1) has been proposed as a promising therapeutic target due to its pivotal role in centrosome clustering to mediate cancer cell progression. This study aimed to analyze the expression and biological function of KIFC1 in CRC. Immunohistochemically, 67 (52%) of 129 CRC cases were positive for KIFC1 and stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Spheroid colony formation having colonies containing numerous CSCs is used to identify genes specific to CSCs [7]. Previously, we performed microarray analyses of spheroid body-forming and parental cells in GC cell lines and reported upregulation of several kinesin genes, including KIFC1 and KIF11 [8-11]. In this study, we explored candidate genes from microarray data and found that the minichromosome maintenance complex component 4 (MCM4) gene was upregulated in the MKN-45 GC cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Spheroid colony formation having colonies containing numerous CSCs is used to identify genes specific to CSCs [7]. Previously, we performed microarray analyses of spheroid body-forming and parental cells in GC cell lines and reported upregulation of several kinesin genes, including KIFC1 and KIF11 [8-11]. In this study, we explored candidate genes from microarray data and found that the minichromosome maintenance complex component 4 (MCM4) gene was upregulated in the MKN-45 GC cell line.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al (31) used bioinformatics to investigate and analyze the differences in gene expression between normal and nasopharyngeal carcinoma tissues and found that significantly high ZWINT expression was related to nasopharyngeal carcinoma tissues. Akabane et al (32) found that KIFC1 was positive in 67 (52%) of 129 patients with colorectal cancer based on immunohistochemistry; this positivity was also found to be related to the low OS rate. Moreover, the expression of ZWINT was found to be significantly correlated with KIFC1 expression, and KIFC1 and ZWINT knockout cells were observed to reduce the tumor formation ability (32).…”
Section: ' Discussionmentioning
confidence: 97%
“…Akabane et al (32) found that KIFC1 was positive in 67 (52%) of 129 patients with colorectal cancer based on immunohistochemistry; this positivity was also found to be related to the low OS rate. Moreover, the expression of ZWINT was found to be significantly correlated with KIFC1 expression, and KIFC1 and ZWINT knockout cells were observed to reduce the tumor formation ability (32). Kim et al (33) found that the invasion and migration abilities of ZWINT-deficient pancreatic cancer cells were decreased; the expression levels of MMP2 and MMP9 were decreased; and the cell cycle arrested in the G2/M phase.…”
Section: ' Discussionmentioning
confidence: 97%
“…For instance, in gastric cancer, miR‐635 suppresses cancer cell proliferation, migration, and invasion by targeting KIFC1 12 . In addition, KIFC1 can upregulate ZWINT expression to promote colorectal cancer progression and sphere formation 13 . Besides, highly expressed KIFC1 promotes cell viability and colony formation in BC cells according to Li et al 14 Nevertheless, a thorough understanding of the mechanism that KIFC1 participates in BC pathogenesis is yet to be discussed, which was also the focus of this study.…”
Section: Introductionmentioning
confidence: 99%